2014
DOI: 10.1002/asia.201403089
|View full text |Cite
|
Sign up to set email alerts
|

An Extremely Bulky Tris(pyrazolyl)methanide: A Tridentate Ligand for the Synthesis of Heteroleptic Magnesium(II) and Ytterbium(II) Alkyl, Hydride, and Iodide Complexes

Abstract: The tris(pyrazolyl)methane compound HC(3-Ad-5-Mepz)3 [1, 3-Ad-5-Mepz=3-(1-adamantyl)-5-methylpyrazolyl] and its regioisomer, HC(3-Ad-5-Mepz)2 (3-Me-5-Adpz), were synthesized and crystallographically characterized. Deprotonation of 1 with MeLi afforded the lithium complex [{κ(3) -N-C(3-Ad-5-Mepz)3 }Li(thf)], which incorporates a tris(pyrazolyl)methanide ligand of unprecedented bulk. Reaction of 1 with MeMgI gave the ionic coordination complex [{κ(3) -N-HC(3-Ad-5-Mepz)3 }MgMe]I, which was readily deprotonated to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
0
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 34 publications
2
27
0
4
Order By: Relevance
“…This is significantly high-field shifted compared to that in the known terminal magnesium hydride complexes [(tBuNacnac)MgH(DMAP)] (d = 4.65 ppm; A), [2e] [(Ar*Nacnac)MgH] (d = 4.07 ppm; B), [4] and [{k 3 N-C(3-Ad-5-Mepz) 3 }MgH] (d = 5.68 ppm; C). [5] Differential scanning calorimetry (DSC) measurements of 3 revealed ad ecomposition temperature of 122 8C, close to that of [{k 3 N-C(3-Ad-5-Mepz) 3 }MgH] (C). [5] Ad ecomposition experiment performed in av olume-reduced NMR tube, as described by Harder et al, [2b] indicated the formation of dihydrogen in the 1 HNMR spectra.…”
mentioning
confidence: 66%
“…This is significantly high-field shifted compared to that in the known terminal magnesium hydride complexes [(tBuNacnac)MgH(DMAP)] (d = 4.65 ppm; A), [2e] [(Ar*Nacnac)MgH] (d = 4.07 ppm; B), [4] and [{k 3 N-C(3-Ad-5-Mepz) 3 }MgH] (d = 5.68 ppm; C). [5] Differential scanning calorimetry (DSC) measurements of 3 revealed ad ecomposition temperature of 122 8C, close to that of [{k 3 N-C(3-Ad-5-Mepz) 3 }MgH] (C). [5] Ad ecomposition experiment performed in av olume-reduced NMR tube, as described by Harder et al, [2b] indicated the formation of dihydrogen in the 1 HNMR spectra.…”
mentioning
confidence: 66%
“…However, aMg À Hspecies was not formed. [10] Thegroups of Nozaki and Hill reported several Mg À Bactivation modes. [11] Based on the literature 11 BNMR values and the Lewis acidity/basicity affinity,t he shift in the 11 BNMR activation of the HBpin is most probably due to adual MgÀOand OÀBcoordination.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…From the different chiral (R)-(+ +)-BINOL scaffolds (1a-h)tested, magnesium complexes of ligand 1a provided the best enantioselectivity (entries 2vs. [7][8][9][10][11][12][13]. Finally,w ei nvestigated the effect of alkali salt additives as they can have an influence on the performance.However, only as light increase in enantioselectivity was observed (entry 14 vs.2 ).…”
mentioning
confidence: 99%
“…This, however, yielded a product mixture with stoichiometric HBpin, including some unreacted 1, and a product mixture with one major L-containing species ( 31 P{ 1 H} NMR resonance: δ 22.8 ppm) if an excess of HBpin is used. As a previously used alternative pathway to an MgH species on a sterically demanding monomeric tris(pyrazolyl)methanide MgnBu complex [35] (10), N(1)-P(1)-C(1)101.55 (13), N(2)-P(2)-C(1) 104.52 (14), P(4)-C(2)-P(3) 125.13 (19), N(3)-P(3)-C(2) 100.99 (14), N(4)-P(4)-C(2) 104.70 (14). (13), N(2)-P(2)-C(1) 104.52 (14), P(4)-C(2)-P(3) 125.13 (19), N(3)-P(3)-C(2) 100.99 (14), N(4)-P(4)-C(2) 104.70 (14).…”
Section: Resultsmentioning
confidence: 99%